Woman's Public Rights in Islamic law and its relevance in the context of Indonesia (Study of Gender Approach) - Hurun Maqshurat Uzlifat Il Jannah (Fak. Syari'ah dan Hukum UIN Sunan Kalijaga, 2013)
ngdm/oen, .01